2003
DOI: 10.1074/jbc.c200619200
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila egghead Encodes a β1,4-Mannosyltransferase Predicted to Form the Immediate Precursor Glycosphingolipid Substrate for brainiac

Abstract: The neurogenic Drosophila genes brainiac and egghead are essential for epithelial development in the embryo and in oogenesis. Analysis of egghead and brainiac mutants has led to the suggestion that the two genes function in a common signaling pathway. Recently, brainiac was shown to encode a UDP-N-acetylglucosamine:␤Man␤1,3-N-acetylglucosaminyltransferase (␤3GlcNAc-transferase) tentatively assigned a key role in biosynthesis of arthroseries glycosphingolipids and forming the trihexosylceramide, GlcNAc␤1-3Man␤1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 32 publications
1
48
0
1
Order By: Relevance
“…We previously identified Egghead (Egh) and Brainiac (Brn) as glycosyltransferases responsible for GSL biosynthesis in Drosophila, catalyzing the addition of the second and third glycosyl residues of the GSL core oligosaccharide chain, respectively (Fig. 1A) (1,2,8). We also showed that egh and brn mutants are devoid of elongated GSLs, demonstrating that these genes are key regulators of GSL biosynthesis (2).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…We previously identified Egghead (Egh) and Brainiac (Brn) as glycosyltransferases responsible for GSL biosynthesis in Drosophila, catalyzing the addition of the second and third glycosyl residues of the GSL core oligosaccharide chain, respectively (Fig. 1A) (1,2,8). We also showed that egh and brn mutants are devoid of elongated GSLs, demonstrating that these genes are key regulators of GSL biosynthesis (2).…”
mentioning
confidence: 72%
“…In Drosophila, extension of glucosylceramide (GlcCer) is exclusively controlled by the mannosyltransferase Egh (Fig. 1A) (2,8). In third instar larvae, we found that loss of egh was often associated with enlargement of the peripheral nerves ( Fig.…”
Section: Egh Mutants Exhibit Enlargement Of Peripheral Nerves With Atmentioning
confidence: 82%
“…Our analysis showed that a specific locus, egh, is needed for robust male courtship behavior (Figure 4). egh encodes a 1,4-mannosyltransferase that regulates glycosphingolipid biosynthesis (Wandall et al 2003), affects Drosophila neural development and behavior, and is required in Ap neurons for female Sex-peptide response post mating (Soller et al 2006). Since ap md544 -Gal4 (a Gal4 insertion in ap) is expressed in the adult nervous system of both sexes ( Figure S2), we examined whether this neural circuit also functioned in males to regulate courtship behavior.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main experimental difficulties in determining the catalytic function of GTs relates to the limited availability of relevant candidate oligosaccharide acceptors. However, the range of possible acceptor structures can be narrowed down by exploiting the observation that monosaccharides can serve as acceptor analogs if provided at high concentrations in the GT assay, also denoted as the free sugar assay (Brü ckner et al, 2000;Wandall et al, 2003). …”
Section: Rgxt1 and Rgxt2 Expressed In Baculovirus-transfected Insect mentioning
confidence: 99%